Anxiety Symptomatology in Severe COVID-19 Survivors and Contributing Factors - Bebiana Manuela Simão da Silva (2022)
Objective: Evidence suggests that severe COVID-19 survivors are at higher risk of developing anxiety symptoms, which may be related to certain risk factors. This study aims to assess anxiety symptoms in these survivors, its contributing factors and the association with concerns reported by survivors regarding COVID-19. Methods: Severe COVID-19 patients admitted in Intensive Care Medicine Department/ICMD of a University Hospital were included, in framework of MAPA prospective project. Exclusion criteria: ICMD stay≤24h, terminal illness, major auditory impairment or inability to communicate at follow-up. Participants were assessed by telephone at follow-up appointment, with Generalized Anxiety Disorder Scale/GAD-7. Survivors' post-discharge concerns regarding discrimination against for COVID-19, infection of families, re-infection or sequelae related to COVID-19 were evaluated. Results: 131 patients were included with 19.9% presented anxiety symptoms. Survivors with higher anxiety were younger, female, had previous psychiatric and respiratory diseases, took more psychiatric drugs and had severe ARDS. Afraid of having COVID-19 again and related sequelae were associated with more anxiety. Conclusions: Anxiety is common in severe COVID-19 survivors, being associated with post-discharge patients concerns, which may limit their daily living. This study emphasizes the importance of psychological assessment and interventions of these survivors, in order to help them in recovery.